2018
DOI: 10.1038/s41557-018-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent membrane tension probe

Abstract: Cells and organelles are delimited by lipid bilayers in which high deformability is essential to many cell processes, including motility, endocytosis and cell division. Membrane tension is therefore a major regulator of the cell processes that remodel membranes, albeit one that is very hard to measure in vivo. Here we show that a planarizable push-pull fluorescent probe called FliptR (fluorescent lipid tension reporter) can monitor changes in membrane tension by changing its fluorescence lifetime as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
538
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 425 publications
(570 citation statements)
references
References 58 publications
29
538
0
3
Order By: Relevance
“…The latter is attractive for concentration‐independent force imaging by FLIM (fluorescence lifetime imaging microscopy) . According to FLIM images of 1 in homogeneous lipid bilayer membranes, the application of tension is reported as linearly decreasing lifetimes, with slopes depending on the lipid composition . This trend is consistent with flipper deplanarization upon lipid decompression (Figure b).…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…The latter is attractive for concentration‐independent force imaging by FLIM (fluorescence lifetime imaging microscopy) . According to FLIM images of 1 in homogeneous lipid bilayer membranes, the application of tension is reported as linearly decreasing lifetimes, with slopes depending on the lipid composition . This trend is consistent with flipper deplanarization upon lipid decompression (Figure b).…”
Section: Introductionsupporting
confidence: 72%
“…Namely, increasing planarization in the ground state will result in increasingly planar FC excited states and thus decreasing losses from relaxation into fully twisted, non‐emissive TICT‐like excited states of 2 . This record mechanosensitivity with regard not only to redshifted excitation but also to fluorescence intensity and lifetime, suggested that CF 3 flipper 2 could, in principle, outperform CH 3 original 1 as fluorescent membrane tension probe in living cells.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Several other derivatives with different headgroups failed to do so (not shown). [5] In summary,these results identify all new members of the double-mutant cycle 1-4 as operational membrane tension probes,w ith general access to chemical stability being the most significant advance,f ollowed by red shifts that add up perfectly to reach important values.T hey introduce doublemutant cycle analysis to fluorescent membrane probes and, most importantly,v alidate an ew,g eneral and fundamental concept that functions with non-trivial supramolecular chemistry,s olves practical problems,a se xemplified with the flipper dilemma, and opens broad new perspectives. This decrease was as for original 1,t hus correctly reporting decreasing membrane tension as tension-induced disassembly of more ordered microdomains.…”
Section: In Memory Of Koji Nakanishimentioning
confidence: 71%
“…

Planarizable push-pull probes have been introduced to demonstrate physical forces in biology.However,the donors and acceptors needed to polarizem echanically planarized probes are incompatible with their twisted resting state.T he objective of this study was to overcome this "flipper dilemma" with chalcogen-bonding cascade switches that turn on donors and acceptors only in response to mechanical planarization of the probe.T his concept is explored by molecular dynamics simulations as well as chemical double-mutant cycle analysis. [5,6] The current best is constructed around twisted dithienothiophene (DTT) dithienothiophene S,S-dioxide (DTTO2) conjugates ( Figure 1a,D ' = S, A' = SO 2 ). [5,6] The current best is constructed around twisted dithienothiophene (DTT) dithienothiophene S,S-dioxide (DTTO2) conjugates ( Figure 1a,D ' = S, A' = SO 2 ).

…”
mentioning
confidence: 99%